SAKSI KELUARGADALAM PENYELESAIAN PERKARA PERCERAIAN PADA PENGADILAN AGAMA - Zikri, A. Hamid Sarong, Dahlan Ali. (Jurnal Ilmu Hukum, 2014)
Abstrack:Each person is considered competent to be a witness, unless the act otherwise provides. Family witness in procedural law of religious court is deemed competent only to a divorce settlement with syiqaq reason. But in practice it is widely used for the disposal of divorce for reasons other than syiqaq. The main researches problems are 1).What is the concept of a family witness in a divorce settlement in religious courts? 2). whether basic considerations of the judge to accept or reject a family witness as evidence for divorce cases in addition to the syiqaq reason? The aim of this research and study, examines the concept of a family witness in a divorce settlement in religious courts and judges reviewing basic considerations in accepting or rejecting the family witnesses as evidence for divorce cases in addition to the syiqaq reason. The research method used is a normative juridical approach to legislation and conceptual approaches. Source of data used are secondary data consisting of primary legal materials, legal materials and secondary legal materials tertiary. The data were then analyzed qualitatively by decomposition prescriptive. The results showed that 1) There are two conceptions of the family witnesses the application in practice of the Religious Court, namely: first, the family witnesses are acceptable for a divorce case with all of the reasons divorce, and second, require the family to witness divorce cases on the grounds syiqaq. Ideally the concept of family witness is must be presented for all divorce cases with all the reasons divorce 2) Admission to the family witnesses for divorce cases besides syiqaq reason considering the closeness of the family witness with the husband and wife which makes the witness knew the households of the litigants more than another. While the rejection of the family witness for reasons other than syiqaq because considering the lack of legal basis, while allowing judges must obey the law and are bound to the terms set forth in the program regulations. Keywords: Familywitnessanddivorce cases. Abstrak: Setiap orang dianggap cakap menjadi saksi, kecuali undang-undang menentukan lain. Saksi keluarga dalam hukum acara peradilan agama dipandang cakap hanya untuk penyelesaian perkara perceraian dengan alasan syiqaq.Namun dalam prakteknya banyak digunakan untuk penyelesaian perkara perceraian dengan alasan selain syiqaq.Masalah pokok penelitian adalah 1).Apakah konsep saksi keluarga dalam penyelesaian perkara perceraian di pengadilan agama? 2).Apakah dasar pertimbangan hakim dalam menerima atau menolak saksi keluarga sebagai alat bukti untuk perkara perceraian selain alasan syiqaq?Penelitian ini bertujuan, mengkaji konsep saksi keluarga dalam penyelesaian perkara perceraian di pengadilan agama dan mengkaji dasar pertimbangan hakim dalam menerima atau menolak saksi keluarga sebagai alat bukti untuk perkara perceraian selain alasan syiqaq.Metode penelitian yang digunakan adalah penelitian yuridis normatif dengan pendekatan perundang-undangan dan pendekatan konseptual.Sumber data yang digunakan adalah data sekunder yang terdiri dari bahan hukum primer, bahan hukum sekunder dan bahan hukum tersier.Data yang diperoleh selanjutnya dianalisis secara kualitatif dengan penguraian preskriptif. Hasil penelitian menunjukkan bahwa 1) Ada dua konsepsi penerapan saksi keluarga dalam praktek di Pengadilan Agama, yaitu :pertama,saksi keluarga dapat diterima untuk perkara perceraian dengan semua alasan perceraian,dan kedua, mengharuskan adanya saksi keluarga untuk perkara perceraian dengan alasan syiqaq. Idealnya konsep saksi keluarga adalah harus dihadirkan untuk semua perkara perceraian dengan semua alasan perceraiannya 2) Penerimaan saksi keluarga untuk perkara perceraian selain alasan syiqaq karena mempertimbangkan kedekatan saksi keluarga dengan suami isteri yang menjadikan saksi keluarga lebih mengetahui keadaan rumah tangga suami isteri yang berperkara tersebut.Sedangkan penolakan saksi keluarga untuk perkara perceraian selain alasan syiqaq karena mempertimbangkan tidak adanya landasan yuridis yang membolehkan sedangkan hakim harus patuh dan terikat pada ketentuan hukum acara yang diatur dalam peraturan perundang-undangan. Kata Kunci:Saksi keluarga dan perkara perceraian